The Errors Analysis On Writing Descriptive Text Made By Students At The 7th Grade Of SMP Muhammadiyah 5 Surakarta In 2015/2016 Academic Year - MALI, KHOLEEYOH, Prof. Dr. Endang Fauziati, M. Hum, Dr. Anam Sutopo, S.Pd. M.Hum (2016)
Mali, Kholeeyoh. A320120079. THE ERRORS ANALYSIS ON WRITING DESCRIPTIVE TEXT MADE BY STUDENTS AT THE 7th GRADE OF SMP MUHAMMADIYAH 5 SURAKARTA IN 2015/2016 ACADEMIC YEAR. Research Paper. Muhammadiyah University of Surakarta. 2016. The study aims at describing the learners‟ error made by seventh grade students of SMP Muhammadiyah 5 Surakarta in their composition of writing descriptive text: Identify the types of lexical errors, syntactical errors, and discourse errors; classification the frequency of each type of errors; describes the dominant type of errors; and identifying the source of errors. The type of this research is descriptive qualitative research. There are three steps to collect data, namely (1) The researcher entered the class and asks students to make a descriptive text, (2) The researcher collected the data of students‟ writing then reads and marks the types of errors that occur in students‟ writing, (3) The researcher documented the erroneous then classifies the type of errors based on linguistic category and surface strategy category. In analyzing the data, the researcher uses James theory for classification of errors, Slamet theory for the frequency of each type of error and Brown, Richard for sources of errors theory. The result of this study shows that seventh grade student‟s of SMP Muhammadiyah 5 Surakarta make 288 errors in their compositions. The writer finds that from 288 data, there are three classifications of error based on the combination of linguistic category and surface strategy taxonomy. First, "Lexical Errors‟ consist of 94 errors or 32.64%. Second, "Syntactical Errors‟ consist of 158 errors or 54.9%. Third, "Discourse Errors‟ consist of 36 errors or 12.5% of errors. The dominant errors from three types are lexical error in wrong spelling consist of 84 errors or 29.17% of errors. The sources error in this research, namely: interlingual transfer and intralingual transfer. Key words: errors analysis, descriptive text, sources of errors, linguistic category taxonomy, and surface strategy taxonomy.